CFD simulation of heating greenhouse using a perforated polyethylene ducts. (2017) - Tadj, Nacima; Nahal, Mohammed Akli; Draoui, Belkacem; Constantinos, Kittas
The location and the power of the heating devices determines in a large extend the flow and temperature patterns inside the greenhouse. The aim of this paper is to analyse the internal convective flows generated in a closed cultivated tunnel greenhouse. Numerical model of greenhouse, which has a size of (20 × 8 × 4.1) m, installing ducting system was evaluated with CFD simulation model (commercially available computational fluid dynamics CFD code CFX-13). The greenhouse was heated by hot air, distributed via clear perforated polyethylene ducts. The standard k-ε model was adopted to describe the turbulent transport. The dynamics' effects of the crop were simulated using the equivalent porous medium approach proposed by Darcy and reorganised by Forshheimer equation. The results are shown in the form of pressure, velocity and temperature contours. Better visualisation of the distribution of these parameters was obtained in order to homogenise the greenhouse climate. The pressure contours along he three perforated ducts show that the discharge through holes is not uniform because of the static pressure difference between upstream and downstream of the hole, as well as the angle and discharge coefficient variation of each hole.